'As solid as and more precious than gold': Gabriel-Julien Ouvrard, John Law and the legacy of the assignats in nineteenth-century France. (13th March 2020) - Greenfield, Jerome
Abstract: It is a truism that the experience of the assignats in the 1790s deterred the French from paper-based wealth during the nineteenth century, a notion that dovetails with a long-standing narrative of French economic backwardness in this period, particularly relative to Britain. This article revisits this interpretation through the study of proposals for public borrowing during the late Empire and early Restoration, most notably those promoted by the financier Gabriel-Julien Ouvrard to finance the payment of reparations after the Napoleonic Wars. Ouvrard's schemes for the mass issuing of bonds embodied ideas that were remarkably similar to those underlying the assignats and John Law's system of 1716–20, which suggests that the French were much less wary of paper assets than historians have assumed.